Abdominal Myolipoma in Dog- a Case Report - Mishra, C; Shah, MK; Mainali, S; Pandey, BR (Nepalese Veterinary Journal, 2023)
A 6-year-old female dog was referred to Veterinary Teaching Hospital of Agriculture and Forestry University, Rampur, Chitwan, Nepal. The complaint was an abdominal mass around the umbilicus centrally and cranial to the sternum without any clinical manifestation. Histopathologically, mature adipocytes of different sizes were seen and were interposed within spindle shaped smooth muscle fibre. The muscle fibres were seen separated due to the proliferative infiltration of these adipocytes in between. Abdominal myolipoma was diagnosed based on the clinical manifestation, gross and histopathological lesions. This could have been misdiagnosed with mammary tumour but the absence of proliferative myoepithelial cells ruled out the possibility.